PLAN DE NEGOCIO PARA PRODUCTOS TURÍSTICOS DE LA FINCA CAFETALERA CHAGUARPAMBA SU CAFÉ, EN EL SECTOR EL JARDÍN, CANTÓN CHAGUARPAMBA, PROVINCIA DE LOJA - Sánchez Chimbo, Rosana Marisol (2017)
ABSTRACT Tourism is now an essential part of the economy of any country and has become a highly competitive activity, to the extent that tourist destinations located in the same country compete with each other. For this reason, the elaboration of a Business Plan plays a fundamental role in the dissemination of tourist attractions and helps economic and social development, considering it as a basic and essential tool for the development of tourism of any destination. Ecuador is no exception, since there are models of business plans that have as main purposes, to increase the number of national and international tourists, to increase the offer of quality tourism, to increase international promotion, as well as to promote sustainable development and improve tourism competitiveness. In the case of the province of Loja, the reality is different, because in the Chaguarpamba canton, there is a great cultural richness, variety of native flora and fauna, natural tourist attractions such as cascades of great scenic beauty, and coffee estates with great Tourist potential. However, at the Finca Cafetalera Chaguarpamba Su Café, which will be called, Finca Cafetalera Chaguarpamba su Café offers the cafeteria service for tourists passing by, but the natural and cultural attractions that it possesses cannot be visited. Lack of a path in the interior, lack of a camping area where tourists can rest and even stay more days in the place, likewise do not have the promotion and necessary dissemination, so they have not been able to be boosted tourist, which generates that the tourist activity in the sector is low and with this it is not possible to create a competitive space in the market. Given this reality, it was decided to carry out the present investigative work "Designing a Business Plan for tourism products of the Chaguarpamba Cafetalera Estate its coffee in the Garden sector, Chaguarpamba Canton, Province of Loja", with the purpose of strengthening tourism and Thereby ensuring a better position within local and national tourism.